Sustainable Development and Global Competitiveness in the Malaysian Timber Council - Muhtar, Suhaili (2024)
This thesis explores the Malaysian timber industry, a critical contributor to the country’s economic growth, but now challenged by global demands for sustainability and competitiveness. My research journey began with identifying the sector’s urgent need for strategies that balance industry viability with environmental stewardship. Focusing on the Malaysian Timber Council (MTC), I employed a qualitative approach, including in-depth interviews and thematic analysis, to investigate the industry’s multifaceted challenges and opportunities. Through interviews with industry stakeholders, policymakers, and MTC representatives, this study analyzes strategic initiatives to strengthen the industry’s sustainability and global competitiveness. Key findings highlight the importance of adopting sustainable forest practices, expanding market access, and integrating technology for manufacturing efficiency and resilience. Additionally, the MTC’s role in promoting technology adoption and supporting supply chain optimization is examined, emphasizing its impact on industry growth. Collaborative efforts, such as partnerships with academia and strategies for securing raw materials, were found essential for sustainable development. The study also evaluates MTC’s role in providing critical market intelligence, fostering transparency, and enhancing stakeholder engagement. Insights reveal that MTC’s credibility and proactive stance in regulatory frameworks are central to its leadership in promoting sustainable practices and trust. In conclusion, this research provides a comprehensive framework for industry resilience, offering policymakers and stakeholders practical insights to drive sustainable development and maintain global competitiveness within the Malaysian timber industry.